Síndrome de Dandy-Walker - Pereira, Carlos Umberto (2001)
A síndrome de Dandy-Walker (SDW) faz parte de um grupo de malformações relacionadas as disgenesias do paleocerebelo._________________________________________________________________________________________ ABSTRACT: This is a brief review on Dandy Walter syndrome. The author analyses the diagnosis and the treatment of the syndrome.